The proximity of political parties. The right way for indigenous electoral participation? Analysis of Monterrey and its metropolitan area - Mendoza Ibarra, José Fredman (2020)
Studies about indigenous political participation become socially relevant at the time of elucidating the problems facing the system of participatory and representative democracy in Mexico and Latin America. Securing the interests and fulfilling the demands of the indigenous population, through the vote, highlights the role of political parties and questions their real functioning in order to provide democratic stability to the political system. In this sense, the link between the indigenous population and political parties becomes essential for democratic development and for the institutionalization of the parties themselves; however, what happens when the indigenous population is in a migratory context such as Monterrey and its metropolitan area in northeast Mexico? How is this link between political parties and indigenous people for the materialization of their demands and democratic stability? Through a qualitative approach using two instruments: semi-standardized interviews and focus groups, tackling the descriptive research hypothesis that stipulated that indigenous electoral clientelism by political parties and indigenous leaders, as well as the limited relationship of the academy and indigenous and pro-indigenous civil society organizations with the indigenous population, it undermines indigenous electoral participation in Monterrey and its metropolitan area. The study shows that the relationship between parties and indigenous people in Monterrey and its metropolitan area is low and, if there is a relationship, it is conditioned to electoral clientelism and ignorance of indigenous political rights. Furthermore, the role of academy and organized civil society is weak in terms of compliance with rights, and the emergence of indigenous leaders who do not have legitimacy in the community turns out to be a threat to democratic consolidation and party institutionalization in Monterrey and its metropolitan area.